Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

What is the solution to the equation 6y –2(y + 1) = 3(y – 2) + 6?
y = –10
y = –2
y = 2
y = 6


Sagot :

Answer:

y = 2

Step-by-step explanation:

6y - 2(y + 1) = 3(y - 2) + 6

6y - 2y - 2 = 3y - 6 + 6

6y - 2y - 2 = 3y

4y - 2 = 3y

4y - 2 + 2 = 3y + 2

4y = 3y + 2

4y - 3y = 3y - 3y + 2

y = 2